Velocity-Based Strength Training: The Validity and Personal Monitoring of Barbell Velocity with the Apple Watch - Basil Achermann; Katja Oberhofer; Stephen J. Ferguson; Silvio R. Lorenzetti (MDPI AG, 2023)
Velocity-based training (VBT) is a method to monitor resistance training based on measured kinematics. Often, measurement devices are too expensive for non-professional use. The purpose of this study was to determine the accuracy and precision of the Apple Watch 7 and the Enode Pro device for measuring mean, peak, and propulsive velocity during the free-weighted back squat (in comparison to Vicon as the criterion). Velocity parameters from Vicon optical motion capture and the Apple Watch were derived by processing the motion data in an automated Python workflow. For the mean velocity, the barbell-mounted Apple Watch (r = 0.971-0.979, SEE = 0.049), wrist-worn Apple Watch (r = 0.952-0.965, SEE = 0.064) and barbell-mounted Enode Pro (r = 0.959-0.971, SEE = 0.059) showed an equal level of validity. The barbell-mounted Apple Watch (Vpeak: r = 0.952-0.965, SEE = 0.092; Vprop: r = 0.973-0.981, SEE = 0.05) was found to be the most valid for assessing propulsive and peak lifting velocity. The present results on the validity of the Apple Watch are very promising, and may pave the way for the inclusion of VBT applications in mainstream consumer wearables.